Procedural Strength, Ethical Weakness: A Component-Based Analysis of EFL Students’ Information Literacy - Ratna Dewanti; Yordan Yasin; Deni Sapta Nugraha; Ikhsanudin Ikhsanudin; Ivonne Frietche Panjaitan (FKIP Universitas Lampung, 2026)
This study examines the information literacy (IL) competencies of EFL students at Indonesian higher education institutions. The study aims to (1) identify overall levels of information literacy competency, (2) examine strengths and weaknesses across five core IL components, (3) describe the distribution of competencies across undergraduate, master’s, and doctoral levels, and (4) determine instructional priorities to inform embedded information literacy development within English education curricula. A descriptive survey design was employed involving 227 undergraduate, master’s, and doctoral students from three Indonesian universities. Data were collected using the 40-item Information Literacy Test (ILT), which assesses competencies in recognizing information needs, locating information, evaluating information, using information, and applying information ethically. Descriptive statistics, non-parametric group comparisons, and correlational analyses were conducted to examine performance patterns across educational levels and IL components. The results indicate that students demonstrated a moderate level of overall information literacy competency, with substantial overlap in score distributions across educational levels. Although postgraduate students achieved slightly higher mean scores than undergraduates, these differences were modest and not statistically significant. Students performed strongest in using information for academic tasks, while lower performance was observed in evaluating information and applying information ethically. The findings suggest that progression through higher levels of formal education does not automatically lead to systematic development of information literacy competencies among EFL students. Persistent weaknesses in evaluative judgment and ethical use of information across educational stages highlight the need for intentional, curriculum-embedded information literacy instruction within English education programs. This study provides an empirically grounded, component-level profile of information literacy competencies to support more coherent and pedagogically aligned instructional practices in Indonesian higher education. Keywords: information literacy, higher education, EFL, information literacy test.